(untitled) (Edad Media. Revista de Historia, 2023)
The archival history of the archive of the monastery of Santa Clara of Barcelona, let us to discover some aspects of the history of the creator that completes and enriches what we know exclusively through the informative content of the documents. In the mid-13th century, with the entry of Pere de Forn as a “donado”, a lay brother, member of the community of Poor Clares, the personal collection of this merchant from Barcelona was incorporated into the monastic archive, with documentation that is typologically very different from the profile of the community archive. What does the archival collection reflect of the creator? Who were the lay bothers in the context of a 13th-century female monastery? Who was he before he joined the monastic family? How was this documentation integrated into the archive and how does it survive within the community archive, with its own documentary practices? Creator and archival fonds will be the central themes around which this article is structured.